Polymer Structures on Surface Acoustic Wave Biosensors. (2017) - Ritter, F.; Hedrich, J.; Deck, M.; Ludwig, F.; Shakirov, D.; Rapp, B.E.; Länge, K.
Abstract: The influence of surface structuring on surface acoustic wave (SAW) biosensor signals has been investigated. Polymer structures on the sensor surfaces were applied by lithography or by self-assembling of polystyrene microparticles. In first experiments, structured and unstructured sensors led to similar results in a model affinity assay using streptavidin and biotinylated protein. On the other hand, structuring had a strong effect on SAW sensor signals obtained by protein adsorption on parylene C coated sensors. Depending on the protein, both decreased (albumin, streptavidin) and increased (fibrinogen) signals were observed with structured SAW sensors. Particularly the latter could contribute to facilitated blood analysis in the future.